Hydraulic fracturing model featuring initiation beyond the wellbore wall for directional well in coal bed. (15th July 2016) - Li, Yuwei; Jia, Dan; Wang, Meng; Liu, Jia; Fu, Chunkai; Yang, Xinliang; Ai, Chi
Abstract: In developing internal fracture systems in coal beds, the initiation mechanism differs greatly from that of conventional ones and initiations may be produced beyond the wellbore wall. This paper describes the features of the internal structure of coal beds and RFPA 2D simulation is used to attest the possible occurrence of initiation beyond the wellbore wall in coal bed hydraulic fracturing. Using the theory of elasticity and fracture mechanics, we analyse the stress distribution in the vicinal coal rock. Then by taking into consideration the effects of the spatial relationship between coal bed cleats and the wellbore, we establish a model for calculating both tensile and shear initiation pressure that occur along cleats beyond the wellbore wall. The simulation in this paper indicates that for shear initiations that happen along coal cleats, the pressure required to initiate fracture for cleats beyond the wellbore wall is evidently lower than that on the wellbore wall, thus it is easier to initiate shear fractures for cleats beyond the wellbore wall. For tensile failure, the pressure required to initiate tensile fracture for cleats beyond the wellbore wall is obviously higher than that for cleats at the wellbore wall, thus it is easier to initiate tensile fractures for cleats at the wellbore wall. On the one hand, this paper has proved the possible occurrence of initiations beyond the wellbore wall and has changed the current assumption that hydraulic fractures can only occur at the wellbore wall. On the other hand, the established theoretical model provides a new approach to calculating the initiation pressure in hydraulic fracturing.